UMPSA explores collaboration with Jonetsu Company Inc. Japan for inclusive ecosystem - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 29 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) explores collaboration with Jonetsu Company Inc. to share expertise and best practices in establishing a sustainable, inclusive ecosystem through international collaboration and networking, with the aim of empowering persons with disabilities (PwD) community through technology, innovation, and education.